1997
DOI: 10.1038/sj.onc.1200881
|View full text |Cite
|
Sign up to set email alerts
|

Strong indication for a breast cancer susceptibility gene on chromosome 8p12-p22: linkage analysis in German breast cancer families

Abstract: Chromosomal losses involving the short arm of chromosome 8 are frequent in a variety of tumor types, including breast cancer, suggesting the presence of one or more tumor suppressor genes in this region. Previous linkage analysis and studies of loss of heterozygosity (LOH) have suggested the presence of a putative third breast cancer susceptibility gene around D8S505 at 8p12-p22. We have performed linkage analysis in two German breast cancer families, showing negative lod scores with 17q and 13q markers, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 10 publications
2
53
0
2
Order By: Relevance
“…10 -12,23 Kerangueven et al 10 and Seitz et al 23 suggested that 8p12-p21 is a locus for a new breast cancer susceptibility gene. Our data do not exclude this possibility and may indeed enhance it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 -12,23 Kerangueven et al 10 and Seitz et al 23 suggested that 8p12-p21 is a locus for a new breast cancer susceptibility gene. Our data do not exclude this possibility and may indeed enhance it.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analyses on BRCAX patients identified several chromosomal regions potentially harbouring other breast cancer susceptibility genes. They include 8p12-p21, 10 13q21, 11 and 2q32, 12 however, they were excluded or need to be evaluated with regards to population specificity. 13 There are no comprehensive molecular cytogenetic studies that report characteristic chromosomal imbalances involved in tumour progression in BRCAX patients.…”
mentioning
confidence: 99%
“…None of the P-values were significant after the correction of Benjamini and Hochberg [1995] (data not shown). A P-value of 6 Â 10 À4 was obtained at the SNP TSC671100 at 26.8 Mbs on chromosome 8p12, which is within a region previously identified by linkage analysis [Kerangueven et al, 1995;Seitz et al, 1997].…”
Section: Genome-wide Snp Ld Mapping Of the ''Test'' Set Approach To Nmentioning
confidence: 96%
“…Nonetheless, in the analysis of the ''test'' data set, P-values close to the significance threshold obtained after correction for multiple testing were achieved in two regions of the genome: one on chromosome 15, and another on chromosome 9. A third region was identified in the haplotype analysis that was identified previously by linkage analysis [Kerangueven et al, 1995;Seitz et al, 1997]. To determine whether these potential associations can be replicated, haplotype-tagging SNPs from the three candidates regions should be genotyped in the ''test'' set, and thereafter the most informative SNPs should be tested in an independently ascertained series of breast cancer cases and controls.…”
Section: P-value Cutoffs and Replicationmentioning
confidence: 99%
See 1 more Smart Citation